ADAPTASI BUDAYA PEKERJA MIGRAN INDONESIA DI TAIWAN - Naga Mulia, Wim; Rahardjo, Turnomo; Qurrota Ayun, Primada (Interaksi Online, 2024)
With over 272 thousand workers by the start of 2024, Indonesia is Taiwan’s largest source of migrant labour (Workforce Development Agency, 2024). Despite the requirement to undergo practical and language training prior to placement in Taiwan, Indonesian migrant workers frequently find difficulties adapting to Taiwanese culture, particularly due to language barriers. Therefore, this study aims to explore the cultural adaptation process of Indonesian migrant workers in Taiwan, and identify obstacles and strategies used for resolution. The theories used in this study are Communication Accommodation Theory and Co-Cultural Theory. It is a qualitative descriptive study with a phenomenological approach, collecting data through in-depth interviews with five Indonesian migrant workers in Taiwan. The findings reveal that adaptation process for migrant workers in Taiwan begins with experiencing culture shock, which includes language barriers and lack of knowledge about work environment. Various communication strategies are employed by Indonesian migrant workers in adapting to cultural differences, such as integration and separation strategy, where differences in communication styles and language are addressed through convergence strategy. Additionally, the research identifies that workers overcome cultural barriers, such as negative societal stigma and discrimination, by employing assertive and aggressive accommodation strategies. Based on these findings, future research should investigate the emergence of these obstacles by delving deeper into the efforts made by migrant workers to overcome them, and consider the host society’s perspective to enrich the data.